2016
DOI: 10.1177/1038416215604002
|View full text |Cite
|
Sign up to set email alerts
|

Career management attitudes among business undergraduates

Abstract: Globalisation, organisational restructuring and new technology have been connected with a shift to ‘protean’ and ‘boundaryless’ career attitudes with workers, including new graduates, increasingly required to be self-reliant in successfully navigating their careers. This study explores protean and boundaryless career attitudes among Business undergraduates and the influence of demographic, background and employment characteristics on these attitudes. Data were collected for Business undergraduates at a UK (N¼8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
(154 reference statements)
1
8
0
Order By: Relevance
“…Each of the forms of professional proficiency helps to encourage the person to continue his or her career where success will be associated with the characteristics and changes that are taken in the workplace (Jackson & Wilton, 2016;Takawira, 2018). That is, decision making will be associated with the set of limitations or development possibilities that the company itself has.…”
Section: Career Limitsmentioning
confidence: 99%
“…Each of the forms of professional proficiency helps to encourage the person to continue his or her career where success will be associated with the characteristics and changes that are taken in the workplace (Jackson & Wilton, 2016;Takawira, 2018). That is, decision making will be associated with the set of limitations or development possibilities that the company itself has.…”
Section: Career Limitsmentioning
confidence: 99%
“…The tension between employers and HE about who should be responsible for providing work-ready graduates is longstanding (e.g. Helyer, 2011;Jackson & Wilton, 2016;Starkey & Tempest, 2008). In the UK, concerted attention across the HE sector to raise the level of employability by developing more vocationally relevant skill-sets in graduates was galvanised to a significant extent by the recommendations of the Dearing Report (1997).…”
Section: Responsibility For Work-readinessmentioning
confidence: 99%
“…. Other specialities (accounting and finance) have been found to be more akin to specific occupational groups in the closer relationship between such qualification and employment (Jackson & Wilton, 2016). However adding a business qualification would be likely to improve job mobility and adaptation options, which would contribute to the popularity of business courses as second-study choices (Baird, 2012), as found in the current research.…”
Section: Group 2 Broadfields: Business; Education; Health; Architecturementioning
confidence: 52%
“…As in the study by Jackson and Wilton, (2016), proponents of the future new career forecasts see increased mobility as desirable, and aim to develop congruent attitudes in graduates. However, in the present research, disjunctive broadfield changes were predominantly from general to more occupationally specific degrees, which have been related to easier initial labour market entry and job stability, but lower career trajectories.…”
Section: Methodological Contributionsmentioning
confidence: 99%